The urgency of vaccination against Covid-19 in dentists - Arriola Guillén, Luis Ernesto (2021)
The requirement of vaccines for the prevention of Covid-19 has become one of the health priorities of different countries worldwide (1, 2). However, most societies still do not have the necessary number of vaccines to cover their entire target population (3, 4). This is especially true in countries that delayed negotiations with the supply companies, and which will, unfortunately, have to wait a long time for the arrival of sufficient quantities to protect their populations. On the other hand, the global vaccination process has established priority levels among its citizens, specifically starting with the so-called first line of action which is health professionals attending to Covid-19 patients, due to the great risk to which they are exposed. Additionally, the health organizations of the different countries have proposed to continue the vaccination process according to different criteria, one being the risk levels of the professions. This criterion is aimed at prioritizing professionals most exposed to contagion, but according to their daily practice, what professionals are really the most exposed to contagion?